2004
DOI: 10.1111/j.1467-7687.2004.00318.x
|View full text |Cite
|
Sign up to set email alerts
|

When left means right: an explanation of the left cradling bias in terms of right hemisphere specializations

Abstract: Previous research has indicated that 70-85% of women and girls show a bias to hold infants, or dolls, to the left side of their body. This bias is not matched in males (e.g. deChateau, Holmberg & Winberg, 1978; Todd, 1995). This study tests an explanation of cradling preferences in terms of hemispheric specialization for the perception of facial emotional expression. Thirty-two right-handed participants were given a behavioural test of lateralization and a cradling task. Females, but not males, who cradled a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
65
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 28 publications
8
65
2
1
Order By: Relevance
“…In contrast, a link between left holding and left visual field advantage in the perception of face stimuli has been found in studies using dolls (Bourne & Todd, 2004;Huggenberger, Suter, Reijnen, & Schachinger, 2009;Vauclair & Donnot, 2005) though no equivalent right visual field advantage appears to be associated with right holding (Bourne & Todd, 2004;Harris et al, 2010). However, when mothers held infants, no correlation between visual field advantage and holding side was found (Donnot & Vauclair, 2007;Vauclair & Scola, 2009;Scola & Vauclair, 2010b).…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…In contrast, a link between left holding and left visual field advantage in the perception of face stimuli has been found in studies using dolls (Bourne & Todd, 2004;Huggenberger, Suter, Reijnen, & Schachinger, 2009;Vauclair & Donnot, 2005) though no equivalent right visual field advantage appears to be associated with right holding (Bourne & Todd, 2004;Harris et al, 2010). However, when mothers held infants, no correlation between visual field advantage and holding side was found (Donnot & Vauclair, 2007;Vauclair & Scola, 2009;Scola & Vauclair, 2010b).…”
mentioning
confidence: 88%
“…If this model were applied to the data from this study, the group of mothers who showed an inconsistent lateral bias would be presumed to have higher levels of fluctuating asymmetry. This kind of variability may go some way towards explaining inconsistencies and discrepancies within the literature regarding associations between infant/doll holding side and measures of hemispheric specialisation (Bourne & Todd, 2004;Donnot & Vauclair, 2007;Harris et al, 2010;Huggenberger et al, 2009;Lucas et al, 1996). It could therefore be informative to compare hemispheric laterality data from participants, especially mothers, who show a consistent lateral cradling preference with those who do not.…”
mentioning
confidence: 98%
“…This type of analysis does not allow estimation of individual preferences, but is often used to assess the one-sided behavioural biases at the population level (Bourne and Todd, 2004;Siniscalchi et al, 2012;Karenina et al, 2017). The first observation of lateral trunk use from each individual was included in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The right hemisphere is known to play a role in the expression and perception of emotional information (e.g., Bryden & Levy, 1983) and could consequently be involved in the regulation of emotional exchanges when a parent holds his or her child. Different investigations (e.g., Bourne & Todd, 2004;Huggenberger et al, 2009;Vauclair & Donnot, 2005) have demonstrated that hemispheric specialization in the perception of facial emotions is correlated with holding-side biases. The main finding is that the left holding bias is linked to enhanced perception of facial emotions in the left visual field, that is, under the control of the right cerebral hemisphere.…”
Section: Introductionmentioning
confidence: 99%
“…The generality of this behavior has prompted growing interest in the literature and some researchers have attempted to explain the origin of this bias. As holding-side preference is a postural asymmetry, several studies have examined the relationship between the side of holding and the presence of other asymmetries expressed by the mother (e.g., perceptual asymmetries and handedness: Bourne & Todd, 2004;Harris, Almerigi, & Kirsch, 2000;Huggenberger, Suter, Reijnen, & Schachinger, 2009;Manning & Chamberlain, 1991;Vauclair & Donnot, 2005) or by the child (e.g., asymmetric tonic neck reflex or ATNR: Bundy, 1979;Ginsburg, Fling, Hope, Musgrove, & Andrews, 1979;Sieratzki & Woll, 1996).…”
Section: Introductionmentioning
confidence: 99%